Možnosti využití koučování v práci stavebních a pozemkových úřadů - Indrová, Martina (Vysoké učení technické v Brně. Fakulta stavební, 2014)
Tato bakalářská práce se zabývá možnostmi využití koučování v práci stavebních a pozemkových úřadů. Cílem je zjistit, jaké povědomí mají zaměstnanci těchto úřadů o koučování a jak jsou spokojeni se stavem vedení a řízení na jejich pracovišti. Výsledkem je formulování závěrů a doporučení, sestavených na základě výsledků z dotazníkového šetření a řízených rozhovorů.

This bachelor’s thesis is dedicated to possibilities of using coaching in the work of building and land offices. The aim of the bachelor’s thesis is to find out what employees of these offices know about coaching and how they are satisfied with the state of leadership and management in their workplace. The result is to formulate conclusions and recommendations, which were compiled from the results of the questionnaire and structured interviews.
The possibilities of using coaching in the work of building and land offices
Keywords: stavební úřad; pozemkový úřad; kouč; koučování; management; building office; land office; coach; coaching; management